2020
DOI: 10.1142/s2424835520500083
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Porous β-Tricalcium Phosphate: A New Bone Filling Substitute for Treatment of Distal Radius Fracture in the Elderly Population

Abstract: Background: A new beta-tricalcium phosphate with unidirectional pore structure (UDPTCP), Affinos® (Kurray, Okayama, Japan), has been in clinical use since 2015. To date, there have been only a few clinical studies using this material. We report here the first clinical study for distal radial fracture in the elderly population treated with UDPTCP. Methods: Consecutive patients aged 65 years or older with dorsally displaced unstable fracture of the distal radius (n = 36) were treated operatively in our departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This study demonstrated that UDPTCP is a useful bone graft material for filling defects after the resection of benign bone tumors. UDPTCP was implanted to fill a bone defect in the treatment of distal radial fractures, and radiographic evaluation showed that UDPTCP implantation with internal fixation for distal radial fractures resulted in the resorption of the implant in the early postoperative period and replacement by the host bone less than one year after surgery [30,31]. In addition, UDPTCP filling resulted in the restoration and preservation of anatomic position after the correction of distal radius fractures in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that UDPTCP is a useful bone graft material for filling defects after the resection of benign bone tumors. UDPTCP was implanted to fill a bone defect in the treatment of distal radial fractures, and radiographic evaluation showed that UDPTCP implantation with internal fixation for distal radial fractures resulted in the resorption of the implant in the early postoperative period and replacement by the host bone less than one year after surgery [30,31]. In addition, UDPTCP filling resulted in the restoration and preservation of anatomic position after the correction of distal radius fractures in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that Affinos has good properties of material resorption and replacement to host bone. Regarding fractures of the distal radius, Muramatsu et al [8] only reported the clinical outcomes of Affinos ® filling in the surgical treatment. The average age in their study was 74 years, and in the present study, it was almost the same as 71 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although no absorption was seen at 3 months when blocks and granules were used for a large bony defect during plate fixation for pelvic fracture, they were completely replaced with the patient's own bone at 18 months [14]. Another institution also reported favorable outcomes with the use of Affinos ® for bony defects during plate fixation in distal radius fractures [15].…”
Section: Trauma Surgerymentioning
confidence: 99%